Natural migration potential of noble metals of Mongol-Okhotsk gold belt - Sergey Mikhailovich Radomskyii (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
In connection with increasing flow of noble metals dispersion in river waterways at high transit speed, it seems relevant to distinguish between man-made and natural migration and determine its potential. The main aim of the study is to assess noble metals (Ru, Rh, Pd, Ag, Os, Ir, Pt, Au) migration potential of Mongol-Okhotsk gold belt in relation to oxidized and reduced forms of biogeochemical components in the Upper and Middle Amur region province. To this effect, the author has developed and tested the methods for determining the oxidized C[NMn+] forms, reduced C[NM] forms, their relations C[NMn+]/C[NM], and evaluating the natural migration potential [ E[migr]=0,059/n * lg(C[a NMn+]/ C[q NM] ]. The methods used in the study: atomic absorption, electrochemistry, photometry, catalysis and chemical analysis methods, using techniques of extraction and assay concentration in determining the mass of ordinary shares in noble metal geochemical samples with an error for the correctness, accuracy and reproducibility of [